MANAGEMENT OF AVASCULAR NECROSIS OF FEMORAL HEAD IN SICKLER PATIENTS BY CORE DECOMPRESSION AND STEM CELLS INJECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background: O.N. of the femoral head, which is common in younger patients with S.C.D. The hip joint will deteriorate to the point of collapse and secondary osteoarthritis if not treated or if non-operative treatment is employed exclusively. Given the unsatisfactory long-term outcomes observed in this patient group after T.H.A., we recommend that patients with early-stage disease preserve their joints. The aim: The point of this study is to find out if core decompression and stem cell therapy are safe, effective, and doable for treating acute venous non-hemolysis in people in our area who have problems with their spinal cord. Material and methods: The 22 hips of S.C.D. patients with A.V.N. of F.H. were the subjects of this prospective study, which ran from October 2012 to July 2014 in the orthopedic department of Basra General Hospital in Basra city, south of Iraq. They were 30 years old on average. Out of the eighteen patients, four (22.22%) showed bilateral involvement with AVN. There was a unilateral effect on 14 patients' reminders (77.77%). Every single patient had an MRI scan before their surgery. This study used a Ficat and Arlet staging approach, which included stages I, II, and III, to statistically examine how visible the disease was on radiographs. We evaluated patients clinically using M.H.H.S. We also approached each patient using the Hardinge method. A sample of stem cells was taken. The next step was to inject stem cells into the damaged area, starting at the anterior iliac crest. This was done after core decompression of the necrotic zone in the femoral head was done under fluoroscopic supervision. Results: The S.C.D. After undergoing core decompression and stem cell therapy for the treatment of AVN of F.H., patients who had previously complained of moderate to severe pain, gait limitation, and functional limitations in their activities reported less or no pain and an improvement in their functional abilities in the four months after surgery. Additionally, a mean M.H.H.S. of 76.2% before surgery provided further support for this. Average MHHS after four months was 88.18%. The highly significant result is indicated by the paired t-test, which has a p-value of less than 0.0001. The outcomes of the clinical examination were more important than those of the radiographic and magnetic resonance imaging (MRI) exams. Conclusion: To prevent the subchondral bone from collapsing even further, which would lead to secondary arthritis and the early need for T.H.A., which has terrible long-term outcomes for those individuals. Treatment of AVN with core decompression and stem cells is considered safe, practical, and effective for S.C.D. patients, particularly those with Ficat and Arlet stages I and II. Conversely, the clinical evaluation outcomes of those patients showed a weaker connection with radiographic and MRI findings.